Comparison of the harmfulness of smoking tobacco cigarettes versus heat-not-burn tobacco in patients with asthma - Nowak, Artur; Pawliczak, Rafał (Alergologia Polska - Polish Journal of Allergology, 2021)
Asthma is a heterogeneous disease characterized by chronic inflammation of the airways with symptoms such as wheezing, shortness of breath, chest tightness and coughing of varying frequency and severity, with varying degrees of airway obstruction. Many factors have a significant influence on the course of asthma, including smoking. The harmful effects of cigarettes have been known for a long time and pose a unique threat to people suffering from asthma. Exposure to passive inhalation of tobacco smoke and active smoking can lead to exacerbation of the disease, wheezing, coughing and shortness of breath. Tobacco smoke irritates the respiratory system and damages the cilia. Continued exposure to cigarette smoke in the environment also increases the risk of other respiratory diseases such as bronchitis, pneumonia and lung cancer.